2009
DOI: 10.1002/ejic.200801229
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Kinetic Studies of the Reactions between Aqua[1‐(2‐aminoethyl)piperazine]palladium(II) and Biologically Relevant Nucleophiles

Abstract: The kinetics and mechanism of the complex-formation reactions of [Pd(AEP)(H 2 O)] 2+ , where AEP stands for 1-(2-aminoethyl)piperazine, with biologically relevant ligands were studied as a function of selected nucleophiles and pH. The reactivity of the ligands follows the sequence L-methionine Ͼ guanosine-5Ј-monophosphate Ͼ glycine Ͼ inosine ϾϾ glutathione. The substitution reactions with glutathione showed two reaction steps in which the first step involves coordination through nitrogen and depends on the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…The purines like inosine have two metal ion binding centres N 1 and N 7 nitrogens. The pH dependent binding of these N-donors was already reported [27]. The results showed that inosine forms the complexes 110 and 111.…”
Section: Complex Formation Equilibria Involving Dna Constituentsmentioning
confidence: 57%
“…The purines like inosine have two metal ion binding centres N 1 and N 7 nitrogens. The pH dependent binding of these N-donors was already reported [27]. The results showed that inosine forms the complexes 110 and 111.…”
Section: Complex Formation Equilibria Involving Dna Constituentsmentioning
confidence: 57%
“…Therefore, Pd(II) complexes are good models for the analogous Pt(II) complexes in solution. Recent work in our laboratories focused on the equilibria of complex-formation reactions of cis-(diamine)PdCl 2 [4][5][6][7][8][9][10][11][12]. In this study, a chelated ligand, N,N-diethylethylenediamine was used.…”
Section: Introductionmentioning
confidence: 99%
“…We have a long-standing interest in equilibria of complex-formation reactions of (diamine)PdCl 2 [21][22][23][24][25][26][27] and dinuclear palladium(II) [28,29] complexes with bio-relevant ligands. It will be of interest to extend these investigations and study the mono-and binuclear complexes with N,S-donor ligands.…”
Section: Introductionmentioning
confidence: 99%